Is the patient able to watch TV or read the newspaper? A functional semi-structured scale to observe Hemineglect symptoms in Activities of Daily Living (H-ADL). Issue 6 (1st November 2016) - Piccardi, L.; Magnotti, L.; Tanzilli, A.; Aloisi, M.; Guariglia, P.
ABSTRACT: We developed a functional semi-structured scale to observe Hemineglect symptoms in Activities of Daily Living (H-ADL). The scale could assist clinicians in assessing rehabilitation priorities aimed at correcting any persisting errors or omissions. In addition, the scale could also be used by caregivers to observe patients' progress and improve their participation. Two groups of right brain-damaged patients (25 with hemineglect; 27 without hemineglect) were tested twice: at admission and before discharge from hospital. A control group of healthy individuals matched to patients for age and education and patients' caregivers also participated. Two raters (A; B), experts in neuropsychology, observed patients and healthy individuals using the H-ADL. We found that the H-ADL final scores correlated with the standard hemineglect tests. The three groups differed in performance and differences also emerged between the first and the second assessment, suggesting an improvement due to the remission of hemineglect as a consequence of the treatment. Raters A and B did not differ in their observations, but there were some discrepancies with caregivers' observations. Therefore, although caregivers could help clinicians in detecting persistent hemineglect behaviour, the assessment should be performed by experts in neuropsychology.